P125 The Irish Lung Fibrosis Association's 2000 Steps A Day Challenge: A Pilot Study To Evaluate A Novel Home Exercise Programme For Lung Fibrosis Patients. (10th November 2014) - Cassidy, N; Byrne, IA; Danaher, D; Egan, JJ
Abstract : Idiopathic Pulmonary Fibrosis (IPF) is a progressive, debilitating interstitial lung disease of unknown aetiology that results in irreversible scarring of the lungs. Patients develop impaired oxygen exchange and subsequent functional limitations including dyspnoea, hypoxia and fatigue. Patients' fear of breathlessness leads to avoidance of physical activity yet, exercise is crucial to maintain health, strength, and mobility. Pulmonary rehabilitation is advocated for IPF patients but access to such programmes is difficult and restricted. Methods: The Irish Lung Fibrosis Association (ILFA) in collaboration with the physiotherapy department at the Mater Misericordiae University Hospital developed the 2000 Steps a Day Challenge as a new and innovative home-based exercise programme for IPF patients. The 2000 Steps a Day pack includes a pedometer, guidance and a diary to progress the step programme, and a Contract for Success to encourage commitment. Positive language and inspirational messages were used to motivate patients to make it part of their daily routine and reassure and support those experiencing setbacks. The programme was piloted by 15 ambulatory patients (11 male: 4 female) for 4-weeks. 10/15 patients required supplementary oxygen, 6/15 patients were on the lung transplant list and 3/15 patients were post-lung transplant. Patients were asked to record their baseline daily step count for 1-week, to gradually incorporate an additional 2000 steps (equivalent to 1 mile of walking) into their daily routine, and to complete a questionnaire on the suitability of the new exercise programme. Results: 12/15 patients completed the pilot phase and successfully added at least 2000 steps extra to their daily routine. 10/12 patients completed the questionnaire. 90% said the written materials were clear and understandable, 70% said the programme was easy to incorporate into their lives, 80% were motivated to exercise every day, 90% considered the pedometer a good motivational tool, 70% found the diary practical, 80% reported improved confidence, 100% felt a sense of achievement after reaching their target, 100% would recommend the programme to another patient. To date, over 200 walking packs have been requested. The ILFA 2000 Steps a Day Challenge is a novel, safe, effective and achievable home-based exercise solution for IPF patients.